2019
DOI: 10.47197/retos.v36i36.66873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de sobrepeso y obesidad, hábitos alimentarios y actividad física y su relación sobre el rendimiento académico (Prevalence of overweight and obesity, exercise, and dietary habits, and their relation with academic achievement)

Abstract: El presente estudio tuvo como objetivo determinar la prevalencia de sobrepeso y obesidad así como evaluar la práctica de actividad física y pautas alimentarias en niños escolares de 3º Ciclo de Educación Primaria y su relación con el rendimiento escolar. Un total de 115 niños de 5 y 6º de Educación Primaria fueron seleccionados en escuelas públicas de Bollullos del Condado (Huelva). La composición corporal se determinó mediante impedancia bioeléctrica (Tanita MC-980), la actividad física mediante el cuestionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
8
1
3
Order By: Relevance
“…In this sense, Esteban-Cornejoet al (2016) reflected that the benefits of adherence to the Mediterranean diet over AP seem to be stronger as young people adhere to the optimal levels of the Mediterranean diet. For example, Iglesias et al (2019) only found that a low consumption of fruits, vegetables, and dairy products was related to a worse AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Esteban-Cornejoet al (2016) reflected that the benefits of adherence to the Mediterranean diet over AP seem to be stronger as young people adhere to the optimal levels of the Mediterranean diet. For example, Iglesias et al (2019) only found that a low consumption of fruits, vegetables, and dairy products was related to a worse AR.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, recent research in primary school students has analyzed the relationship between the quality of the diet and AP (Alfonso Rosa, Álvarez Barbosa, & del Pozo Cruz, 2018;Esteban-Cornejo et al, 2016;Faught et al, 2017;Iglesias, Planells, & Molina López, 2019;McIsaac, Kirk, & Kuhle, 2015;Nyaradi et al, 2016;Pearce et al, 2018;Vassiloudis, Yiannakouris, Panagiotakos, Apostolopoulos, & Costarelli, 2014). A systematic review reflects that there are moderate associations between the dietary intake characterized by the consumption of foods rich in energy and poor in nutrients and the general quality of the diet with respect to the results of the AP (Burrows, Goldman, Pursey, & Lim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The problems of excess weight of the Region may be related to the low proportion of active population and the high number of population that remains inactive, requiring a lot of effort to systematically increase the performance of physical activity of the school environment and for it to extend to the family and the community (Cuadri Fernández, et al, 2017;Iglesias et al, 2019;Alvarez et al, 2020). The reported data is not optimistic about the school health problem in the short, medium and long term in the Region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have reported a positive association between maintaining a healthy diet and practicing regular physical exercise on academic performance [9][10][11][12][13]. However, some studies have reported an inadequate dietary intake in this population, including insufficient consumption of fruit and vegetables, and an excessive consumption of meat, sweets, and sugary drinks [14,15]. Other factors contributing to a less than optimal lifestyle in this population include digital transformation, which has increased the use of screens and, subsequently, reduced daily physical activity [14].…”
Section: Introductionmentioning
confidence: 97%
“…However, the evidence on the association between lifestyle and academic performance is not clear. On the one hand, some studies have observed weak or non-significant associations between diet and academic performance [9,15,24,25]. On the other hand, previous studies have not found an association between regular physical exercise and academic performance [12,15,26].…”
Section: Introductionmentioning
confidence: 99%